1992
DOI: 10.1073/pnas.89.18.8691
|View full text |Cite
|
Sign up to set email alerts
|

Brain and gastrointestinal cholecystokinin receptor family: structure and functional expression.

Abstract: Cholecystokinin was one of the first gastrointestinal peptides discovered in the mammalian brain. In the central nervous system there is evidence for CCKA and CCKB receptor subtypes. The CCKA receptors occur in a few localized areas of the central and peripheral nervous systems where they modulate feeding and dopamine-induced behavior. CCKB receptors occur throughout the central nervous system where they modulate anxiety, analgesia, arousal, and neuroleptic activity. We have recently purified and cloned a CCKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(114 citation statements)
references
References 44 publications
2
111
0
1
Order By: Relevance
“…Several receptor (R)-subtypes bind gastrin and choecystokinin octapeptide (CCK)-like peptides. Cholecystokinin type 1 receptor (CCK 1 R) mainly bind CCK-like peptides and have negligible affinity for gastrins (Kopin et al, 1992;Wank et al, 1992). Cholecystokinin type 2 receptor (CCK 2 R) bind amidated gastrins and CCK with almost equal affinity, but demonstrate negligible affinity for non-amidated gastrins (Kopin et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several receptor (R)-subtypes bind gastrin and choecystokinin octapeptide (CCK)-like peptides. Cholecystokinin type 1 receptor (CCK 1 R) mainly bind CCK-like peptides and have negligible affinity for gastrins (Kopin et al, 1992;Wank et al, 1992). Cholecystokinin type 2 receptor (CCK 2 R) bind amidated gastrins and CCK with almost equal affinity, but demonstrate negligible affinity for non-amidated gastrins (Kopin et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of mouse CCKB-R mRNA was assessed by RT-PCR (Super Script Preamplification System, GIBCO) using 5Ј-CTTTGATGGTGATAATGACAGCGA-3Ј and 5Ј-GCACGTAGCAGCCATCACTGT-3Ј by amplifying the 155-bp DNA for the mRNA encoding a part of the third loop of CCKB-R (12,46,47). These primers also amplify the 349-bp genomic DNA for the same region including the 194-bp intron, which was used as a control.…”
Section: Animalsmentioning
confidence: 99%
“…CCKA-Rs exhibit a 500-to 1,000-fold higher affinity for sulfated analogs of CCK than for gastrin, whereas CCKB-Rs have approximately equal affinity for both sulfated and non-sulfated peptide analogs of CCK and gastrin (32,34,46,47). CCKB-Rs are present in parietal, ECL, and probably somatostatin cells (2,4,23,27,28,41 (2,28).…”
mentioning
confidence: 99%
“…CCK interacts with at least two distinct types of receptor (Innis & Snyder, 1980;Moran et al, 1986;Wank et al, 1992): CCKB receptors, which represent the predominant form in the rodent CNS (Pelaprat et al, 1987;Hill & Woodruff, 1990) and CCKA receptors, the abundant form in peripheral tissues (Zetler, 1984;Van Dijk et al, 1984;Chang & Lotti, 1986) but are also found in discrete nuclei of the CNS (Hill et al, 1987a;. Molecular cloning and pharmacological studies have demonstrated a close relationship between CCKB and gastrin receptors found mainly in the parietal cells of the gastric mucosa (Chang et al, 1989;Pisegna et al, 1992;Hunter et al, 1993).…”
Section: Introductionmentioning
confidence: 99%